Optimalisasi Mahasiswa KKN Berbasis Masjid Di Desa Lubuk Gilang Kecamatan Air Periukan Kabupaten Seluma - Riska Nopiani; Dela Athalla; Meisa Monika; Rales Eko Putra; Rahmi Natalia Piranda; Putri Handayani; Apriana Apriana; Dahliana Dahliana; Alya Dwi Afriani; Heni Nopita Ariani; Zora Meidianda (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Real Work Lecture (KKN) activities for Fatmawati Soekarno Bengkulu State Islamic University (UIFAS) students are a forum for students to carry out community service activities. The aim of this service activity is to serve the community through real and beneficial activities for the community. This activity was carried out in Lubuk Gilang Village, Air Periukan sub-district, Seluma Regency. The community service carried out by the 148 UINFAS Bengkulu group is mosque-based. Mosque-based community service is one form of effort to strengthen the role of mosques as centers of religious activities as well as centers of social empowerment. This research aims to evaluate the effectiveness of various community service programs implemented in mosques, such as teaching the Koran, Blessing Friday, Clean Friday, cleaning graves, commemorating 1 Muharram, banana resilience programs and activities to become teaching staff in schools. The methodology used in this research is a qualitative approach with data collection techniques through observation, interviews and documentation. The research results show that these programs have a positive impact on the surrounding community, both in increasing religious knowledge, building social awareness, and maintaining a clean environment.